Effect of mild hypothermia-assisted stereotactic hematoma puncture and catheter drainage on postoperative intracranial pressure and neuroprotection in elderly patients with intracerebral hemorrhage - Kai-cheng XIANG; Yi-hua LUO (Chinese Journal of Contemporary Neurology and Neurosurgery, 2018)
Objective To analyze the effect of mild hypothermia-assisted stereotactic hematoma puncture and catheter drainage on postoperative intracranial pressure (ICP) and neuroprotection in elderly patients with intracerebral hemorrhage (ICH). Methods A total of 116 elderly ICH patients randomly underwent stereotactic hematoma puncture and catheter drainage (control group, N = 58) and mild hypothermia-assisted stereotactic hematoma puncture and catheter drainage (combination group, N = 58). ICP, serum S-100B protein (S-100B) and blood glucose were monitored. European Stroke Scale (ESS) was used to evaluate neurological function, and Glasgow Coma Scale (GCS) was used to assess conscious state. Results ICP increased after operation, and reached the peak on the 3rd day, and then decreased, but was still higher than immediately after operation on the 7th day in both groups (control group: t = 55.232, P = 0.000; t = 74.233, P = 0.000; t = 67.583, P = 0.000; t = 59.642, P = 0.000; t = 52.852, P = 0.000; t = 45.865, P = 0.000; combination group: t = 28.765, P = 0.000; t = 54.233, P = 0.000; t = 33.402, P = 0.000; t = 27.379, P = 0.000; t = 16.122, P = 0.000; t = 7.444, P = 0.000). The serum S-100B (control group: t = 9.443, P = 0.000; t = 12.952, P = 0.000; t = 18.832, P = 0.000; combination group: t = 11.454, P = 0.000; t = 15.404, P = 0.000; t = 20.439, P = 0.000) and blood glucose (control group: t = 11.580, P = 0.000; t = 14.592, P = 0.000; t = 17.482, P = 0.000; combination group: t = 12.343, P = 0.000; t = 15.231, P = 0.000; t = 19.631, P = 0.000) on the 3rd, 5th and 7th day in both groups were significantly lower than immediately after operation. The ESS scores 2, 4, 12, 24 and 48 weeks after operation were significantly higher than immediately after operation (control group: t = 30.533, P = 0.000; t = 39.273, P = 0.000; t = 43.853, P = 0.000; t = 48.924, P = 0.000; t = 53.322, P = 0.000; combination group: t = 38.943, P = 0.000; t = 43.595, P = 0.000; t = 49.923, P = 0.000; t = 52.594, P = 0.000; t = 58.943, P = 0.000). The GCS score on the 1st and 7th day after operation were significantly higher than before operation in both groups (control group: t = 10.434, P = 0.000; t = 15.232, P = 0.000; combination group: t = 13.432, P = 0.000; t = 17.532, P = 0.000). Compared with control group, ICP (F = 111.553, P = 0.000), serum S-100B (F = 9.834, P = 0.000) and blood glucose (F = 8.094, P = 0.001) were significantly lower, while ESS score (F = 10.689, P = 0.000) and GCS score (F = 7.343, P = 0.007) were significantly higher in combination group. There was no significant difference on the mortality between 2 groups [6.90% (4/58) vs. 5.17% (3/58); adjusted χ2 = 0.000, P = 1.000]. No patient suffered from epidural hematoma or intracranial infection. Conclusions Mild hypothermia-assisted stereotactic hematoma puncture and catheter drainage can significantly reduce ICP in elderly ICH patients, and improve the neurological function and conscious state.